Impact of patient selection on performance of an early rule-out pathway for myocardial infarction: from research to the real world. (3rd October 2022) - Bularga, A; Kimenai, D M; Taggart, C; Lowry, M; Wereski, R; McCance, K; Lee, K K; Anand, A; Strachan, F E; Tuck, C; Shah, A S V; Chapman, A R; et al.
Abstract: Background: Early rule-out pathways for myocardial infarction using high-sensitivity cardiac troponin are widely recommended in the assessment of patients with suspected acute coronary syndrome. Although developed in selected patients participating in research studies, these pathways are applied more widely in clinical practice where the diagnostic performance and effectiveness of these pathways may differ. Purpose: To evaluate the performance of an early rule-out pathway for myocardial infarction using high-sensitivity cardiac troponin in selected and consecutive unselected patients with suspected acute coronary syndrome. Methods: Presentation and serial high-sensitivity cardiac troponin I concentrations were measured in two cohorts of patients with suspected acute coronary syndrome presenting to the Emergency Departments across three acute care hospitals in Scotland. In the unselected cohort, electronic health record data were collected on consecutive patients in whom the usual care clinician measured cardiac troponin for suspected acute coronary syndrome. In the selected cohort, patients with suspected acute coronary syndrome were approached between 8am and 8pm by research staff and written informed consent obtained. In both cohorts, the performance of the High-STEACS early rule-out pathway was evaluated for an adjudicated diagnosis of myocardial infarction (type 1, type 4b or type 4c) during the index hospital admission. Results: The unselected and selected patient cohorts comprised of 1, 242 (median age 60 [interquartile range 47–75] years, 46% women) and 1, 695 (median age 61 [52–73] years, 40% women) patients respectively. Myocardial infarction was diagnosed in 6% (74/1, 242) and 14% (232/1, 695) of patients in the unselected and selected patient cohorts respectively. More patients had myocardial infarction ruled-out in the unselected (74% [828/1, 112] versus 66% [1, 102/1, 678]; P<0.001), with similar negative predictive value (99.9% [95% CI 99.7%-100%] versus 99.7% [95% CI 99.4%-99.0%) and sensitivity (99.3% [95% CI 97.4%-100%] versus 98.9% [95% CI 97.6%-99.9%]; Figure 1). In the selected cohort, more patients had intermediate troponin concentrations requiring serial testing (36% versus 29%) or had myocardial infarction diagnosed (34% versus 26%; P<0.001 for both). In contrast, the positive predictive value for myocardial infarction was lower in unselected patients (26.1% [95% CI 21.2%-31.4%] versus 39.9% [95% CI 35.9%-44.0%]). Conclusion: The prevalence of myocardial infarction is lower in patients with suspected acute coronary syndrome evaluated in routine practice compared to those selected to participate in a research study. Whilst more patients have myocardial infarction accurately ruled out, the positive-predictive value in those ruled in is lower resulting in more hospital admissions with elevated cardiac troponin due to other conditions. Funding Acknowledgement: Type of funding sources: Public grant(s) – National budget only. Main funding source(s): British Heart FoundationMedical Research Council